Gary Becker's Contributions in Health Economics - Rodrigo R. Soares (Institute for the Study of Labor (IZA), 2014)
This short essay reviews Gary Becker's contributions and influence in health economics. It was originally prepared for the collection of short papers in honor of Gary Becker that is scheduled to appear in the inaugural issue of the Journal of Demographic Economics.
Keywords: I1; J1; 330; Gary Becker; health; human capital